Associations of the Weekend Warrior Physical Activity Pattern with All-Cause, Cardiovascular Disease and Cancer Mortality: The Mexico City Prospective Study - De Moraes-Ferrari, G (BMJ Publishing Group, 2024)
Objectives The objective was to investigate the benefits of the’weekend warrior’ physical activity pattern in Latin America, where many people take part in high levels of non-exercise physical activity. Methods Participants in the Mexico City Prospective Study were surveyed from 1998 to 2004 and resurveyed from 2015 to 2019. Those who exercised up to once or twice per week were termed weekend warriors. Those who exercised more often were termed regularly active. Analyses were adjusted for potential confounders. Results The main analysis included 26 006 deaths in 154 882 adults (67% female) aged 52±13 years followed for 18±4 years (mean±SD). Compared with those who reported no exercise, the HR (95% CI) was 0.88 (0.83 to 0.93) in the weekend warriors and 0.88 (0.84 to 0.91) in the regularly active. Similar results were observed for cardiovascular disease and cancer mortality, but associations were weaker. Stratified analyses showed that substantial reductions in all-cause mortality risk only occurred when the duration of exercise sessions was at least 30–60 min. The repeated-measures analysis included 843 deaths in 10 023 adults followed for 20±2 years. Compared with being inactive or becoming inactive, the HR was 0.86 (95% CI 0.65 to 1.12) when being a weekend warrior or becoming a weekend warrior and 0.85 (95% CI 0.70 to 1.03) when being regularly active or becoming regularly active. Conclusions This is the first prospective study to investigate the benefits of the weekend warrior physical activity pattern in Latin America. The results suggest that even busy adults could benefit from taking part in one or two sessions of exercise per week. © Author(s) (or their employer(s)) 2024.